2015
DOI: 10.1002/asi.23357
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evaluation of metadata for video games and interactive media

Abstract: Despite increasing interest in and acknowledgment of the significance of video games, current descriptive practices are not sufficiently robust to support searching, browsing, and other access behaviors from diverse user groups. To address this issue, the Game Metadata Research Group at the University of Washington Information School, in collaboration with the Seattle Interactive Media Museum, worked to create a standardized metadata schema. This metadata schema was empirically evaluated using multiple approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

7
0

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 16 publications
0
46
0
Order By: Relevance
“…In a series of user studies conducted as part of this research effort, both mood and visual style have been identified as potentially useful elements for accessing games. In an online survey involving 1,257 participants, 66.7% responded that mood/affect information would be useful for the games they are currently playing or for seeking new games to play, and 53.4% for visual style [7]. Of the 237 respondents who reported having game-related professions, 70.9% and 55.3% responded positively for mood/affect and visual style, respectively.…”
Section: Previous Research Effortsmentioning
confidence: 88%
See 3 more Smart Citations
“…In a series of user studies conducted as part of this research effort, both mood and visual style have been identified as potentially useful elements for accessing games. In an online survey involving 1,257 participants, 66.7% responded that mood/affect information would be useful for the games they are currently playing or for seeking new games to play, and 53.4% for visual style [7]. Of the 237 respondents who reported having game-related professions, 70.9% and 55.3% responded positively for mood/affect and visual style, respectively.…”
Section: Previous Research Effortsmentioning
confidence: 88%
“…Of the 237 respondents who reported having game-related professions, 70.9% and 55.3% responded positively for mood/affect and visual style, respectively. Interview data from 56 game users [7] also supports the importance of such metadata: Based on the user data, we decided to include visual style and mood in our video game metadata schema. In order to consistently describe these attributes, it is necessary to establish a controlled vocabulary for each element.…”
Section: Previous Research Effortsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 21 The motivation for the project was to provide a framework for standardized description and organization of video games and interactive media. This is necessary because other existing schemas and standards such as Dublin Core (DC), FRBR (Functional Requirements for Bibliographic Records), Resource Description and Access (RDA), Cataloging Cultural Objects (CCO), CIDOC Conceptual Reference Model (CIDOC CRM) are often too broad and/or not as relevant for describing specific information objects such as video games.…”
Section: Prior Work On Access To Video Gamesmentioning
confidence: 99%